96 WELL, HIGH THROUGHPUT TRANSLATION. (2002) - Allen Allen, Jason Jason; Wallace Wallace, Janette Janette; Patel Patel, Meenal Meenal; Kudlicki Kudlicki, Wieslaw Wieslaw
Abstract : Ambion has developed 96 well protein expression systems using a bacterial extract for coupled transcription/translation and a eukaryotic rabbit reticulocyte lysate for translation. Each well is designed for high reproducibility and a high yield of full-length target proteins. These systems are ideal for large scale screening assays and high throughput analysis.